High coordination and equitable parental effort in the Rufous Hornero - Massoni, Viviana (2012)
In temperate regions of the Southern Hemisphere, avian parental care is understudied, in particular for the neotropical family Furnariidae. We measured rates of nest building, mud carrying, incubation, brooding, feeding, and nest-sanitation behaviors of molecularly sexed Rufous Horneros (Furnarius rufus) nesting in the humid pampas of Argentina. We also evaluated the coordination of all these behaviors between the partners, and compared the frequency of uncoordinated behaviors of each sex. Males and females worked equitably throughout the nesting cycle with few exceptions: (1) both sexes built the nest, but males supplied somewhat less mud at the beginning of nest construction, (2) though highly involved in incubating the eggs males did so slightly less often than females during early incubation, (3) even if males also brooded the nestlings, they brooded less often and for slightly briefer periods than did females, and (4) young nestlings were fed less often by males than by females. We found no differences in nest-sanitation rates. The proportion of behaviors coordinated between partners performing different parental tasks was very high through the entire nesting cycle. Analysis of the frequency of uncoordinated behaviors revealed females were more prone than males to skip turns only at the onset of nest building and the beginning of the nestling period. The sexes' similar and coordinated effort is probably essential for the building of the Rufous Hornero's remarkable nest and reaching the high rate of nest success that characterizes the species.